2014
DOI: 10.1159/000360069
|View full text |Cite
|
Sign up to set email alerts
|

Oral versus Short-Term Intratympanic Prednisolone Therapy for Idiopathic Sudden Hearing Loss

Abstract: Objectives: To assess the therapeutic effectiveness of an intratympanic (IT) steroid protocol compared to a systemic steroid protocol. Methods: A total of 265 consecutive patients presenting unilateral idiopathic sudden sensorineural hearing loss were divided into 2 groups. One group comprised 131 patients enrolled between May 2009 and May 2010, and the other consisted of 134 patients enrolled between June 2010 and June 2011; a total of 48 patients were excluded among the 2 groups. The first group received ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
2
19
0
4
Order By: Relevance
“…A previous study reported that a high-dose IT steroid administration for 3 consecutive days within 15 days from the onset of the ISSNHL would lead to a therapeutic success rate of 79.4% [8]. These results have recently been confirmed on a larger sample when IT prednisolone was administered as first line therapy, with a success rate of 73.6% [5]. Correspondence The present study aimed to evaluate the possible relationships between the therapeutic success of IT prednisolone therapy and the age of the patients with ISSNHL, also considering the role played by additional factors, such as time lapse between the onset of ISSNHL and the beginning of treatment (named 'delay'), gender, and pre-treatment hearing levels.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…A previous study reported that a high-dose IT steroid administration for 3 consecutive days within 15 days from the onset of the ISSNHL would lead to a therapeutic success rate of 79.4% [8]. These results have recently been confirmed on a larger sample when IT prednisolone was administered as first line therapy, with a success rate of 73.6% [5]. Correspondence The present study aimed to evaluate the possible relationships between the therapeutic success of IT prednisolone therapy and the age of the patients with ISSNHL, also considering the role played by additional factors, such as time lapse between the onset of ISSNHL and the beginning of treatment (named 'delay'), gender, and pre-treatment hearing levels.…”
Section: Introductionmentioning
confidence: 72%
“…In the clinical practice, three main intra-tympanic (IT) steroid protocols are used applied in ISSNHL: IT steroids alone, combined IT and systemic steroids and salvage IT treatment after failure with systemic steroids [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…A pioneering study by Wilson et al demonstrated that oral corticosteroids could effectively reverse SHL with a recovery rate of 61%, as compared with a placebo recovery rate of 32% [2]. Additional studies have since demonstrated SHL recovery rates of 57–66% with oral corticosteroid use [3,4]. More long-term courses of oral corticosteroids are used in the treatment of AIED, which presents as progressive bilateral asymmetric sensorineural hearing loss (SNHL) occurring over weeks to months, with possible vestibular deficit [57].…”
Section: Introductionmentioning
confidence: 99%
“…In other types of inner pathologies, such as sudden sensorineural hearing loss, the evidence for the benefit of oral steroids has been equivocal [Wei et al, 2013]. When compared to transtympanic steroids for sudden hearing loss, oral steroids were found to be less beneficial [Filipo et al, 2014]. Perhaps alternative routes for systemic drug delivery such as intravenous or intramuscular routes should be studied.…”
Section: Discussionmentioning
confidence: 99%